Physical activity throughout adolescence and bone mineral density in early adulthood: the 1993 Pelotas (Brazil) Birth Cohort Study - Bielemann, R. M. (Springer London, 2014)
SUMMARY: Association between three physical activity (PA) measurements throughout adolescence and bone density at 18 years of age was investigated. PA was associated with both lumbar spine and femoral neck bone mineral density (BMD) in early adulthood independent of type of PA used in the analysis. The results were more consistent in boys. INTRODUCTION: This study amis to evaluate if PA during adolescence could influence BMD later in life. METHODS: A population-based birth cohort study was carried out. PA was assessed at 11 and 15 years of age by questionnaire and included sports performed while BMD (lumbar spine and femoral neck) was measured by dual-energy X-ray absorptiometry at 18 years. A peak strain score was generated based on ground reaction forces of different PA. PA was measured as peak strain score, peak strain score multiplied by minutes/week and minutes/week. Unadjusted and adjusted analyses were performed using linear regression. RESULTS: Overall, 3,811 adolescents were studied (1,866 boys and 1,945 girls). The peak strain score at 11 and 15 years was associated with lumbar and femoral neck BMD at 18 years in boys. Among girls, high-impact PA at 11 years was positively associated with lumbar and femoral BMD (p = 0.01; p < 0.001). After adjusted analysis, weekly minutes of PA at 11 years were not associated with lumbar spine but were associated with femoral neck BMD (p < 0.001); at 15 years, weekly minutes of PA were positively associated with BMD at both sites. Regardless of PA status at 11 years of age, attaining the recommendations of PA (300 min/week) at 15 years appears to be important for BMD at 18 years in both sites in boys and girls. The results Appeared to be more consistent in boys. CONCLUSIONS: PA during adolescence was positively associated with both lumbar spine and femoral neck BMD in early adulthood independent of type of PA used in the analysis.